2014
DOI: 10.1177/0021998314561810
|View full text |Cite
|
Sign up to set email alerts
|

Progressive failure analysis of CFRP laminate with interacting holes under compressive loading

Abstract: Composite structures such as hull of a ship and wings of aircraft are subjected to compressive loading. The behavior and strength of carbon fiber-reinforced polymer (CFRP) panels subjected to tensile loading has been studied rigorously by various researchers, whereas compressive behavior is not well addressed. In this study, behavior of CFRP panel with multiple interacting holes of various configurations (1H, 2HL, 2HT, and 2HD) under compressive loading is studied. A three-dimensional finite element-based prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
(32 reference statements)
1
9
1
Order By: Relevance
“…Varying results have been reported for compression modulus of CFRP depending on the fabrication method and fiber content. Typical values of compression modulus range from 85 to 100% of its tension modulus …”
Section: Experimental Investigationsmentioning
confidence: 99%
“…Varying results have been reported for compression modulus of CFRP depending on the fabrication method and fiber content. Typical values of compression modulus range from 85 to 100% of its tension modulus …”
Section: Experimental Investigationsmentioning
confidence: 99%
“…In the scientific literature, the effect of interacting holes in the in-plane stress concentration factor has been studied, analysing the influence of geometric parameters such as the distance between the holes and the relative radius between the two holes [26][27][28][29][30]. Another geometry parameter that has been studied is the angular position of the holes in relation to the load direction [26,[29][30][31]. Also, the influence of ply orientations and the stacking sequence have been analysed [28,32].…”
Section: Introductionmentioning
confidence: 99%
“…In compression, fibre microbuckling in the plies orientated at 0°is the governing failure mechanism. Depending on the stacking sequence, fibre microbuckling [26,36] or matrix cracking [31] appear first. Afterwards, the damage in the laminate grows, with a combination of failure modes (fibre and matrix damage that leads to delamination failure).…”
Section: Introductionmentioning
confidence: 99%
“…However, in field applications such as wings of aircraft and hull of the ship mostly experience compression under service load. Hence, the behaviour of the composite structure under compressive loading is of greater interest and needs to be thoroughly studied (Khedkar et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have attempted to study the compressive failure of the composite laminate. A considerable amount of experimental and numerical studies (Deng et al., 2017; Guynn and Bradley 1989a, 1989b; Khedkar et al., 2015; Soutis and Fleck, 1990; Soutis et al., 1993; Zhou et al., 2017) have been carried out to investigate the compressive behaviour of the CFC panel with cutout. It has been reported that the failure mechanism in all laminates is mostly due to the micro-buckling in the [0°] plies along with the delamination between off-axis and [0°] plies.…”
Section: Introductionmentioning
confidence: 99%